Aplikasi Pengenalan Produk Menggunakan Augmented Reality dengan Metode Marker - Nurul Bahiyah; Petrus Sokibi; Imam Muttaqin (Jurnal Sistem Cerdas, 2020)
Product introduction is an effort made by a company to introduce new products to the public. However, sometimes there are several obstacles that cause sellers to be unable to show their products to potential buyers, such as during this pandemic. There are many ways to introduce a product, namely through photos or videos. At this stage, a marketing strategy is needed so that the target market is more familiar with the products being sold and can be used as business advantages. Marketing strategies can be done by utilizing technology, one of which is by using Augmented Reality. In augmented reality, there are three characteristics that form the basis of the system, including a combination of the real and virtual worlds, real-time interactions, and the last characteristic is the shape of an object in the form of a three-dimensional or 3D model. The Augmented Reality model used in this study uses the marker method and the application can be applied to an Android smartphone. By using augmented reality technology, the introduction of a product will feel more interactive and effective. In addition, it can increase the product's marketing appeal.